2018
DOI: 10.3390/agronomy8060080
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Map of a Gene Controlling Zero Tannins (zt-1) in Faba Bean (Vicia faba L.) with SSR and ISSR Markers

Abstract: Faba bean (Vicia faba L.), a partially allogamous species, is rich in protein. Condensed tannins limit the use of faba beans as food and feed. Two recessive genes, zt-1 and zt-2, control the zero tannin content in faba bean and promote a white flower phenotype. To determine the inheritance and develop a linkage map for the zt-1 gene in the faba bean germplasm M3290, F 2 and F 3 progenies were derived from the purple flower and high tannin content genotypes Qinghai12 and zt-1 line M3290, respectively. Genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…also identi ed ve genes that control protein content in faba bean. Gutierrez et al (2007) identi ed two SCAR markers tightly linked to a gene controlling tannin de ciency in faba beans and Hou et al (2018) screened one SSR marker (SSR84) closely linked to the tannin content (zt-1) gene using 596 SSR markers and 100 ISSR markers, which could aid in accurate prediction of the zt-1 genotypes.…”
Section: )mentioning
confidence: 99%
“…also identi ed ve genes that control protein content in faba bean. Gutierrez et al (2007) identi ed two SCAR markers tightly linked to a gene controlling tannin de ciency in faba beans and Hou et al (2018) screened one SSR marker (SSR84) closely linked to the tannin content (zt-1) gene using 596 SSR markers and 100 ISSR markers, which could aid in accurate prediction of the zt-1 genotypes.…”
Section: )mentioning
confidence: 99%
“…Later, Webb et al () developed a SNP (single nucleotide polymorphism) marker for ZT1 using a set of SNP markers derived from the genome of the fully sequenced model legume species Medicago truncatula. Recently, Hou et al () reported a reliable SSR (simple sequence repeat) marker that predicted zt1 genotypes with high accuracy. A robust breeder‐friendly molecular marker for zt2 gene is not yet available for faba bean.…”
Section: Introductionmentioning
confidence: 99%
“…Initial experiments focused on lines NV641 and NV676, which were similar in morphology but differed in the absence/presence of spots and their floral VOCs. We were interested in spot presence as this trait is associated with the nutritional content of the crop (Hou et al., 2018), and we wanted to determine if this would lead to any trade‐offs with bee preference. Additional experiments explored more subtle variation in spot size, choosing the extremes of our dataset as bees were most likely to be able to discriminate between them.…”
Section: Methodsmentioning
confidence: 99%